SPIRITUALITAS MISTIS DI BALIK EKSPRESI KESENIAN RAKYAT JARANAN - Alkaf, Mukhlas (Acintya, 2009)
Jaranan is a piece of dance tradition belonged to Lencoh village, Selo district, town of Boyolali in Central Java. The existence of this dance tradition kind of thing has a special reason to be researched and it’s attemption to expose a relationship among misticism and a saveral aspects of the living society itself. Through this article this research will strives the object in depth based on a discipline of anthropology in order to examine interrelation amongst a set of value belong to the village society which is supported way of live into them. From this domain a set of meaning simbolized and accompanied their way of live instead on balance values, and commnal values which is formed by their own costums, historicism, and spirit. According to this article mentioned an ethnographic method with strong emphases into several attemption optimalization of balance pattern founded by misticism values itself. In other way, it focused on the existence of jaranan dance tradition as a little tradition arts had relationship with religiousities view an misticism entirely could be studied by a stressing its cultural text can not be separated by anthropological aspects of dance studies. It will means Jaranan as a little dance tradition can be studied in the whole misticism aspects in the Lencoh village itself.Keyword : misticism, Jaranan dance, symbolism, society, ethnography